Insights from electrical resistivity tomography on the hydrogeological interaction between sand dams and the weathered basement aquifer - Ritchie, Hannah; Holman, Ian P.; Nyangoka, Justus; Bauman, Paul; Parker, Alison (Elsevier, 2024)
Sand dams, composed of recent alluvial aquifers behind concrete dam walls, are a water management technique in drylands. However, their level of hydraulic connectivity with their surrounding weathered basement aquifer is debated. This study aims to constrain this hydrogeological uncertainty in order to better understand their ability to meet water needs and improve dryland water security. The study is the first to use 2D geophysics (Electrical Resistivity Tomography) to provide evidence of seepage from sand dams at three mature and three newly built sites. A generally greater hydraulic connectivity was found between sand dams and their surrounding aquifer than has been assumed in some previous studies, with sites providing at least some local recharge rather than existing as isolated storage structures. This improved understanding is beneficial for both site selection and the performance of sand dams and can help ensure that maximum benefits are derived from the construction of a sand dam depending on its intended purpose.
Data supporting this study are openly available in the Cranfield University repository (CORD) at https://dspace.lib.cranfield.ac.uk/handle/1826/20712.
Keywords: Geophysics; Alluvial aquifer; Kenya; Drylands; Managed aquifer recharge; 3707 Hydrology; 37 Earth Sciences; 3705 Geology; 6 Clean Water and Sanitation; Geochemistry & Geophysics; 3704 Geoinformatics; 4104 Environmental management